Post Rhinoplasty Fibrosis and Collagenase - Munir Abdulmoula; Abdulaziz Bayoo (AlQalam Journal of Medical and Applied Sciences, 2024)
This study aims to explain the technique used to correct the soft tissue pollybeak deformity by utilizing intralesional injection of collagenase. We present our approach, procedure, and treatment regimen for addressing the soft tissue pollybeak using collagenase injection. We provide data from a group of 19 patient who underwent rhinoplasty. Collagenase was administered to 19 patients presented with soft tissue pollybeak deformity. Among these patients, 14 patient (74%) achieved satisfactory results with notable supratip definition, and 5 patients (26%) of the 19 patients experienced suboptimal outcomes, displaying residual supratip fullness according to the surgeon’s assessment. Given the challenges and potential complications associated with revision surgery, the intralesional collagenase injection stands as the primary treatment for soft tissue pollybeak deformities caused by subdermal scarring. In cases where the deformity remains unaddressed after intralesional injection, revision rhinoplasty can be considered as a subsequent option تهدف هذه الدراسة إلى شرح التقنية المستخدمة لتصحيح تشوه الأنسجة الرخوة في منقار الأنف باستخدام حقن الكولاجيناز داخل الآفة. نقدم نهجنا وإجراءاتنا ونظام العلاج لمعالجة تشوه الأنسجة الرخوة في منقار الأنف باستخدام حقن الكولاجيناز. نقدم بيانات من مجموعة من 19 مريضًا خضعوا لجراحة تجميل الأنف. تم إعطاء الكولاجيناز لـ 19 مريضًا يعانون من تشوه الأنسجة الرخوة في منقار الأنف. من بين هؤلاء المرضى، حقق 14 مريضًا (74٪) نتائج مرضية مع تحديد ملحوظ لطرف الأنف، وشهد 5 مرضى (26٪) من المرضى الـ 19 نتائج دون المستوى الأمثل، حيث أظهروا امتلاءًا متبقيًا في طرف الأنف وفقًا لتقييم الجراح. ونظرًا للتحديات والمضاعفات المحتملة المرتبطة بجراحة المراجعة، فإن حقن الكولاجيناز داخل الآفة يمثل العلاج الأساسي لتشوهات الأنسجة الرخوة في منقار الأنف الناتجة عن ندبات تحت الجلد. في الحالات التي يظل فيها التشوه دون علاج بعد الحقن داخل الآفة، يمكن اعتبار عملية تجميل الأنف التصحيحية كخيار لاحق